UPAYA PENYUSUNAN MASTERPLAN INVESTASI DI KABUPATEN BREBES SEBAGAI IMPLIKASI PELAKSANAAN OTONOMI DAERAH - Caroline Caroline; Abdul Syakur (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
Implementation of Regional Autonomy which has been running for approximately 10 years in Brebes requires a lot of cost, it would require a special attraction for investors willing to invest in Brebes. Starting from this thought, required the preparation of Brebes Investment Master plan, which is expected to spur economic growth and increase revenue Brebes. The conclusions of this study is: based on SWOT analysis that has to be got 2 (two) strategic positions, namely: Strategic Position I: Industry, in this position take advantage of all opportunities in the industrial sector is to survive the competition of industry, namely the development and optimization of existing potential, the increase in industrial infrastructure. Strategic Position IV: agriculture, animal husbandry, fisheries, tourism in this position needs to be prioritized development strategy is the diversification of products to increase sales volume.